Inflammatory changes in optic nerve after closed-head repeated traumatic brain injury: Preliminary study. (14th October 2016) - Tzekov, Radouil; Phifer, Josie; Myers, April; Mouzon, Benoit; Crawford, Fiona
Abstract: Background : Closed-head, repeated, mild traumatic brain injury (r-mTBI) leads to inflammatory and degenerative changes in the optic nerve of young wild type mice. This work has investigated whether similar changes may be present when the same model is applied to htau mice, a transgenic mouse in which the non-mutated human tau gene is expressed on a null murine tau background. Methods : This study investigated neuropathological changes in the optic nerve in both young (15 weeks) and old (65–70 weeks) htau mice at 24 hours after r-mTBI or anaesthesia only (r-sham). Change in the level of cellularity, myelin content and astroglial reactivity were evaluated in optic nerve samples. Results : Increased cellularity and areas of demyelination were clearly detectable in the intracranial portion of the optic nerve in both young (10–15 weeks) and old (65–75) htau r-mTBI mice at 24 hours post-injury, in contrast to r-sham. Increased astroglial reactivity was also observed, together with increased tau phosphorylation. Conclusions : Localized inflammatory and degenerative response of the intracranial part of the optic nerve was detected in htau mice after r-mTBI. Further studies to clarify the cause and consequences of this phenomenon are warranted.